Research and Design of Distributed Parallel Processing Cloud CTI System Architecture - Qing Li; Wenhong Zhou (Dianxin kexue)
CTI is responsible for the agent registration management，scheduling management in call center.Therefore，the CTI system’s stability and performance of the integrated call center platform，the scale of the robustness of the agents will have a direct impact.Based on the research of distributed computing，a high reliability，parallel processing of call center cloud CTI system architecture was provided，as well as the dynamic of the system in the call center agent resources and scheduling need matching method，in order to improve the running stability of the large-scale，the ultra large scale call center platform flat core network element CTI system and the convenient of platform smooth expansion.